A Survey on Secured Online Voting System Using Face Recognition - Fugat Ashlesha, G; Gaikwad Shital, Gaikwad Shital; Gangurde Jyoti, P; Sawant Aishwarya, S (International Journal of Computer Sciences and Engineering, 2025)
Now a day, voting for any social issue is important for modern democratic societies. The manual voting system is implemented for election from many years in our country. We are using face recognition to secure the system. The image captured at the time of registration as well as login phase is stored into the cloud database. The converted images are then matched by applying matching criteria which will be we decide. If match is found then and then only the user can proceed for voting Otherwise, the user is considered as invalid user or voter. For confirmation of voting, SMS will send to the voter from server to indicate voting is done successfully.